Haiti : Staff-Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Since 2018, Haiti has experienced a protracted political crisis, repeated country lock-downs and civil unrest, an earthquake, the assassination of its president and a deep recession. Policymakers face economic imbalances, a surge in gang violence, worsening poverty conditions, and dire social challenges aggravated by years of political instability.